Flow naturalisation using hydrological models national hydrology meeting, Institution of Civil Engineers, London, 17 March 1994 (Thomas Telford, 1994)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of BHS national meeting held in March 1994.
Keywords: Hydrologic models -- Congresses.; elektronické knihy; electronic books